Effects of Y Additions on the Microstructures and Mechanical Behaviours of as Cast Mg–xY–0.5Zr Alloys. Issue 4 (18th January 2022) - You, Sihang; Huang, Yuanding; Dieringa, Hajo; Maawad, Emad; Gan, Weimin; Zhang, Yaping; Kainer, Karl Ulrich; Willumeit-Römer, Regine; Hort, Norbert
Abstract : Previous investigations demonstrated that rare‐earth elements (REs) could improve their creep properties effectively. Herein, the influence of Y content on the creep properties of magnesium is investigated systematically with different amount of Y additions. The mechanisms responsible for creep deformation are clarified by the analysis of stress exponent and microstructural characterizations. It is found that the addition of Y in Mg can improve both the ambient strength and high temperature strength owing to its effective solid solution strengthening. At room temperature, the yield strength of Mg–Y alloys has a linear relation with the content of Y. When tested at high temperatures, the yield strength reduces. Compared with pure magnesium, Mg–Y alloys exhibit a high thermal stability even above 200 °C. Small amount of Y addition can improve the creep resistance of Mg largely. With further increasing its content, its contribution to the improvement of creep resistance is weakened for Mg. Under the applied stresses 60–100 MPa and at temperatures of 200–250 °C, the responsible creep mechanism is dislocation controlled. During creep deformation, the Y segregation regions play an important role in hindering the movement of dislocations. Abstract : The addition of Y in Mg improves both the ambient strength and high temperature strength owing to its effective solid solution strengthening. At room temperature, the yield strength of Mg–Y alloys has a linear relation with the content of Y. Small amount of Y addition increases the creep resistance of Mg largely. The responsible creep mechanism is dislocation controlled.